Sleep and its interferent in learning - Nogaro, Arnaldo; Ecco, Idanir; Nogaro, Ivania (Faculdade de Filosofia e Ciências, 2018)
The article results from a bibliographical research, of a qualitative nature, in works and authors that have been concerned with approaching the subject of sleep and its relationship with learning. The goal is to demonstrate how sleep interferes or establishes different interfaces with learning. The intensification of studies on the subject is anchored in the discoveries of new technologies of study of the brain and the knowledge coming from different areas that are concerned with the lifestyle of the human being in the contemporary society. Knowledge of the positive effects of sleep or the consequences of their absence or inadequate quality is imperative for parents and educators to help their children and students to sleep better and better, consequently predispose to the conditions to learn more and have quality of life. Recebido em: 05/05/2017.Aprovado em: 10/09/2018.